Relationship Between Inventory Management And Profitability: Evidence From Selected Manufacturing Firms In Sétif - Bouadam, Faiza; Maiza, Messaoud Amir (جامعة الوادي - University of Eloued, 2022)
This study aimed to test the relationship between working capital management and the profitability of Algerian small and medium enterprises in the province (wilaya) of Sétif, through a sample of (68) enterprises. The validity of the hypotheses was tested according to the panel data model. Statistically significant results were reached between the variables, as there is a direct relationship between inventory management and the rate of return on assets (ROA).
مقال
Keywords: working capital ; enterprise profitability ; inventory turnover rate